Preimplantation genetic testing for Cockayne syndrome with a novel ERCC6 variant in a Chinese family - He, Xuemei; Zhang, Yiyuan; Huang, Xianjing; Qiu, Pingping; Ji, Hong; Ding, Lu; Shi, Yingying; Huang, Yanru; Li, Ping; Mei, Libin (Frontiers in Genetics, 2024)
Background: Cockayne syndrome (CS) is a rare, multisystem, autosomal recessive disorder characterized by cachectic dwarfism, nervous system abnormalities, and premature aging. Mutations in the ERCC6 and ERCC8 genes are the predominant causes of Cockayne syndrome, with ERCC6 gene mutations present in approximately 75% of cases. Methods: Trio-based whole-exome sequencing (trio-WES) was employed to identify potential pathogenic variants associated with CS.Preimplantation genetic testing for monogenic disorders (PGT-M) was conducted to prevent the transmission of the pathogenic variant. Results: Two compound heterozygous mutations were identified in ERCC6-c.1297G>T (p. Glu433*) and c.1607T>G (p. Leu536Trp)-with c.1297G>T representing a novel mutation. Four blastocysts resulting from intracytoplasmic sperm injection were subjected to biopsy. Genetic analyses revealed that E1 harbored maternal mutations in diploid embryos, E2 and E3 carried both paternal and maternal mutations in non-diploid embryos, and E4 did not carry paternal or maternal mutations in diploid embryos. Following the transfer of the E4 embryos, a single successful pregnancy was achieved. Conclusion: The successful application of PGT-M in this family offers a potential approach for addressing other monogenic diseases. The findings of this study broaden the variant spectrum of ERCC6 and will contribute to the molecular diagnosis and genetic counseling of CS. This case highlights the feasibility and effectiveness of PGT-M in preventing CS and provides valuable insights for similarly affected families.